Duodenal strongyloidiasis and hyperinfection syndrome: Case report and literature review - Hassan, Imman Fuad Khattab; de Farias, Bruna Brandão; Kopereck, Vagner Vencato; Jannke, Heitor Alberto; da Silva, José Francisco Pereira; Real, Gustavo Gonzales (Clinical and Biomedical Research, 2016)
Strongyloides stercoralis is an intestinal nematode that commonly causes chronic and asymptomatic infection, but in some situations, especially in cases of immunosuppression, infection by this parasite can manifest with extreme severity and high mortality. Hyperinfection syndrome and disseminated strongyloidiasis are two serious, life-threatening presentations associated with immunosuppression. We report the case of a 69 year-old male with diffuse abdominal pain, intermittent diarrhea, and fever. Stool analysis for parasitic infection was negative. Upper gastrointestinal endoscopy with duodenal biopsy revealed ulcerative duodenitis due to strongyloidiasis, showing the presence of several larvae in lymph and intraglandular ducts. Definitive diagnosis was established as S. stercoralis hyperinfection syndrome.